Anaerobic Bacteria of Antarctica─Isolation of Clostridia from the Soil around Syowa Station─ - Miwa, Toshio (1976)
P(論文) From the soil (permafrost, moraine, bottom of lake, coast, etc.) collected in the area around Syowa Station which is located on East Ongul Island in Lutzow-Holm Bay of Antarctica, a total of 150 strains of clostridia were isolated. Aerobic sporeforming bacteria were isolated less than clostridia. The soil samples, when heated at 80℃ for lOmin or more before the cultivation, proven no Clostridium. One hundred and fifty strains were assigned to 6 species, i.e., C. perfringens, C. bifermentans, C. sordellii, C. fallax, C. sporogenes and C. septicum. The first three species were isolated very frequently and C. sporogenes less frequently. All the strains of C. sordellii were non-toxigenic and had almost the same biochemical and cultural characteristics as those of C. bifermentans except the urease reaction. It was surprising that many clostridia were found in the soil sampled from places which were considered to be scarcely contaminated by human beings and animals. The peculiar distribution and taxonomy of clostridia in the soil of Antarctica are discussed in this paper. departmental bulletin paper